2021
DOI: 10.1016/j.msard.2021.103236
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine hesitancy among people with multiple sclerosis

Abstract: Background:The current severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic has raised awareness of vaccine hesitancy. Specific reasons for vaccine hesitancy among people with multiple sclerosis (pwMS) have not been fully described. Notably, pwMS may experience higher morbidity from vaccinepreventable diseases such as influenza, pneumococcal disease, and human papillomavirus (HPV)-associated warts and malignancies. Furthermore, screening for immunity against measles, mumps and rubella (MMR) is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…In general, the greatest vaccine-hesitant respondents’ concern was about the possible vaccine side effects which are confirmed by other studies ( Yap et al., 2021 ; Ehde et al., 2021 ; Xiang et al., 2021 ; Uhr and Mateen, 2021 ). Therefore, informing the patients about vaccine safety sounds necessary.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In general, the greatest vaccine-hesitant respondents’ concern was about the possible vaccine side effects which are confirmed by other studies ( Yap et al., 2021 ; Ehde et al., 2021 ; Xiang et al., 2021 ; Uhr and Mateen, 2021 ). Therefore, informing the patients about vaccine safety sounds necessary.…”
Section: Discussionsupporting
confidence: 77%
“…They found its association with higher awareness of one's risk of infection with COVID-19 and a higher level of education. Safety concerns were also found as the main cause for SARS-CoV-2 vaccine hesitancy in the study by Yap et al. (2021 ).…”
Section: Introductionmentioning
confidence: 82%
“…This rate of vaccine hesitancy is lower than reported in several countries at a similarly early stages of vaccine accessibility (20-40%) ( Diem et al, 2021 , Ehde et al, 2021 , Xiang et al, 2021 , Serrazina et al, 2021 ). We found no effect of age, sex or educational level on attitudes, which was similar to some reports ( Ehde et al, 2021 , Serrazina et al, 2021 , Yap et al, 2021 ) but not others ( Ehde et al, 2021 , Xiang et al, 2021 , Ghadiri et al, 2021 , Huang et al, 2021 , Uhr and Mateen, 2021 ). Our findings were consistent with evidence, except for one early paper, that lockdowns don't decrease hesitancy ( Caserotti et al, 2021 , Cascini et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…This mirrors the lack of general vaccine promotion by healthcare professionals reported in the UK. ( Yap et al, 2021 )…”
Section: Discussionmentioning
confidence: 99%
“…This rare postvaccine entity was observed with the vector‐based ChAdOx1nCoV‐19 and Ad26.COV2.S SARS‐CoV‐2 vaccines is probably caused by platelet‐activating antibodies against platelet factor 4, mimicking autoimmune heparin‐induced thrombocytopenia and currently named vaccine‐induced immune thrombotic thrombocytopenia (VITT) [ 37 , 38 ]. However, even though decision‐making can be supported by an advantageous risk–benefit profile from phase 3 trials and real‐world evidence, vaccine skepticism is reported among people living with neurological disorders, for example, epilepsy and MS [ 39 , 40 , 41 , 42 ]. Morover, diminished humoral immune responses after SARS‐CoV‐2 vaccination in people with neurological disorders on CD20‐depleting agents and S1P receptor modulators call for individualized vaccination strategies [ 43 , 44 , 45 ].…”
Section: Risk–benefit Profile Of Sars‐cov‐2 Vaccination: Neurological...mentioning
confidence: 99%